The Romanization Policy in the Proconsular Province of Africa and the Resistance of the Libyan Tribes During the Roman Empire (27 BC–429 AD) (Al-Jabal Journal of Humanities and Applied Sciences, 2024)
This research paper studies the Romanization policy and the resistance of the Libyan tribes to it in the Proconsular Province of Africa during the Roman Empire, from 27 BC, the beginning of the establishment of the Proconsular Province of Africa, until the Vandal invasion of North Africa in 429 AD. This paper examines the establishment of the Proconsular Province of Africa and its geographical borders, the policies pursued by the Romans to Romanize the Proconsular Province of Africa, and the position of the Libyan tribes regarding the Romanization policy.
Keywords: Brococonsular Africa; settlement; empire; Romans; Libyan tribes